Analisis Efisiensi Biaya Persediaan Bahan Baku Menggunakan Metode Economic Order Quantity: Studi Kasus di UMKM Silvy Collection - Rufaidah, Anik; Rosyidi, Moh. Ririn (Jurnal Studi Multidisiplin Qomaruna, 2023)
Raw material inventory is crucial for companies as it relates to the amount of stock and frequency of orders. Silvy Collection SME is an industry engaged in the production of hijabs. This SME faces challenges with the stock of raw materials like fabric, thread, and foam, which often result in surplus or excess. This research aims to optimize the cost of purchasing raw materials such as fabric, thread, and foam in this SME through forecasting for the next 12 periods or one year. Forecasting is conducted using the Time Series method, followed by Economic Order Quantity (EOQ) calculations for the period from September 2022 to August 2023. The results indicate a need for 10 rolls of fabric, 49 rolls of thread, and 3 rolls of foam. The total raw material inventory cost according to the company's policy amounts to IDR 1,282,436,960, while using the EOQ method it is IDR 1,278,175,153. The expenditure incurred by Silvy Collection SME is IDR 450,821,525, whereas using the EOQ method it is IDR 450,738,704. The total raw material inventory cost calculated using the EOQ method can save IDR 82,821 or 0.02% compared to the company's policy.